Discovery of novel PC‐PLC activity inhibitors. (19th December 2019) - Zhao, YanChun; Su, Le; Li, Kunlun; Zhao, BaoXiang
Abstract: Phosphatidylcholine‐specific phospholipase C (PC‐PLC) is one of the important members of phospholipase family which is capable of specifically hydrolyzing the third phosphate linker of glycerophospholipid molecules, releasing phosphocholine and diacylglycerols (DAG). It is a crucial virulence factor of bacteria contributed to cell‐to‐cell spread and leading multiple diseases in mammals. Moreover, PC‐PLC has a wide range of biological functions and involves in various cell signaling pathway, including apoptosis, proliferation, differentiation, and metastasis. In this study, we have synthesized 2 chiral compounds ( (R)‐7‐amino‐2, 3, 4, 5‐tetrahydrobenzo[b][1, 4]oxazepin‐3‐ol, called R‐7ABO, and (S)‐7‐amino‐2, 3, 4, 5‐tetrahydrobenzo[b][1, 4]oxazepin‐3‐ol, called S‐7ABO) and discovered their inhibitory effect on PC‐PLC activity which derived from Bacillus cereus ( B. cereus ) and human umbilical vein endothelial cells (HUVEC). Therefore, as two novel efficient PC‐PLC inhibitors, R‐7ABO and S‐7ABO might become favorable tools of antibacterial therapy in B. cereus infection diseases and researching the function of PC‐PLC in HUVECs. Abstract : We synthesized 2 chiral compounds R‐7ABO and S‐7ABO which could inhibit PC‐PLC activity in Bacillus cereus and HUVECs. R‐7ABO and S‐7ABO inhibited PC‐PLC activity more effectively than D609.